Occurrence of Ehrlichia ruminantium and Rickettsia africae in Amblyomma variegatum ticks in selected regions of Zambia - Stoltsz, Wilhelm Heinrich (University of Pretoria, 2023)
Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2023.